Exploring the determinants of regional health governance modes in the Global South: A comparative analysis of Central and South America. Issue 4 (17th October 2021) - Agostinis, Giovanni; Parthenay, Kevin
Abstract: What explains the variation in how states collectively deal with public health challenges across different regions? We tackle this puzzle by comparing the regional health governance efforts pursued within the Central American Integration System (SICA) and the Union of South American Nations (UNASUR). We show that Central America's health governance has been driven by external actors, whereas South America's was driven by states within the region, and remained insulated from external actors' influence. We argue that the explanation for such variation lies in the interplay of state capacity and regional leadership. In Central America, weak state capacity combined with the absence of a regional leader willing to provide governance resources. This opened up space for external actors to contribute actively to regional health governance, complementing the governance of Central American governments. In South America, Brazil's regional leadership mobilised neighbouring states' capacities by promoting a South-South cooperation agenda based on intra-regional exchanges among national health bureaucracies, which, however, proved vulnerable to intergovernmental conflicts. Through the comparison of Central and South America, the article bridges the gap between global health governance scholarship and comparative regionalism, providing new insights on the determinants and effects of regional health governance modes in the Global South.